Effect of black garlic (Allium sativum) on gonadosomatic index, follicle-stimulating hormone level and spermatozoa quality: A study in monosodium glutamate-exposed rat model - Bani, Ika I.; Zulkarnain, Zulkarnain; Gholib, Gholib; Syahrizal, Dedy; Nugraha, Taufiq P.; Ramadhan, Akmal; Akmal, Muslim; Maulina, Nora (Narra Sains Indonesia, 2024)
Infertility rates have risen significantly, one of which is due to monosodium glutamate (MSG) consumption. Recent studies have shown that flavonoids in black garlic (Allium sativum) act as antioxidants. The aim of this study was to assess the effect of black garlic extract (BGE) on gonadosomatic index, follicle-stimulating hormone (FSH) levels, and spermatozoa quality in rats exposed to MSG. Twenty-five healthy rats, aged ten to twelve weeks, were divided equally into five experimental groups: (1) negative control (NC), no intervention; (2) positive control (PC), fed with MSG 8 mg/kg; and (3) fed with MSG + BGE 200 mg/kg; (4) fed with MSG + BGE 400 mg/kg; and (5) fed with MSG + BGE 600 mg/kg. Oral MSG was administered once a day for two weeks before BGE administration was started for two weeks. The measured endpoints were gonadosomatic index, FSH levels, and spermatozoa concentration and quality (spermatozoa motility and abnormality). Analysis of variance (ANOVA) followed by Duncan's post hoc analysis was used to assess the measurement differences. The result suggested that the administration of BGE did not significantly affect the gonadosomatic index (p=0.513). Significant decreases in FSH levels (p=0.005) and spermatozoa concentration were observed in the PC group compared to other groups (p<0.001). Additionally, spermatozoa motility was significantly lower in the PC group compared to NC, BGE200, BGE400, and BGE600 (p<0.001), with higher motility noted in BGE200, BGE400, and BGE600 compared to PC (p<0.001). Furthermore, PC had significantly higher spermatozoa abnormalities compared to NC, BGE200, BGE400, and BGE600 (p<0.001). In conclusion, administration of BGE had a significant effect on the improvement of FSH levels and the quality of spermatozoa in rats exposed to MSG.